2000
DOI: 10.1590/s0301-80592000000300018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the age of the pupal holotissue on the nutritional quality of artificial diets for Trichogramma spp. (Hymenoptera: Trichogrammatidae)

Abstract: The nutritional quality of artificial diets composed of pupal holotissues of Diatraea saccharalis (Fabr.) (Lep.: Crambidae) from three different age classes (1-2, 3-4 and 5-6 days old) were tested for rearing Trichogramma galloi Zucchi and T. pretiosum Riley (Hym.: Trichogrammatidae) in vitro. Pupal holotissues were added to egg yolk, bovine fetal serum, lactoalbumine hydrolysate and preservatives, and offered to the parasitoids into artificial eggs. The quality of these diets in supporting the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Total amount of available protein during adulthood strongly affects reproduction (vitellogenins) (Fortes et al , 2011). Cônsoli & Parra (2000) showed that rearing Trichogramma galloi Zucchi and T. pretiosum Riley on artificial diets containing high amounts of protein led to an increased number of produced eggs. It seems that lower fecundity of low quality reared wasps may be due to less protein available during embryo growth and adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Total amount of available protein during adulthood strongly affects reproduction (vitellogenins) (Fortes et al , 2011). Cônsoli & Parra (2000) showed that rearing Trichogramma galloi Zucchi and T. pretiosum Riley on artificial diets containing high amounts of protein led to an increased number of produced eggs. It seems that lower fecundity of low quality reared wasps may be due to less protein available during embryo growth and adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Development of the three trichogrammatid species was tested on a standard diet, composed of D. saccharalis pupal holotissues (65%), egg yolk (18%), bovine fetal serum (8.5%), albumin hydrolysate (8.5%), and streptomycin sulfate (0.3%), which was developed for Trichogramma pretiosum Riley and Trichogramma galloi Zucchi (Cônsoli & Parra, 2000). Preparation and collection of the pupal holotissues of D. saccharalis , diet preparation, and artificial egg preparation followed Cônsoli & Parra (2000).…”
Section: Methodsmentioning
confidence: 99%
“…However, the quality of pupal holotissues as a component of artificial diets for Trichogramma was also dependent on the age at which the pupal tissues were collected. Older the pupae, lower the parasitoid development and survivorship (Cônsoli and Parra 2000). Although several Trichogramma species could be reared on diets containing hemolymph/holotissues of one of these insects, not all species or populations from a same species tested would properly parasitize artificial eggs filled with such diets, or complete their embryonic and/or larval development.…”
Section: Artificial Diets -Compositionmentioning
confidence: 99%
“…One of the major obstacles of producing parasitoids in the latter conditions is the fact that the artificial culture medium has to provide the adequate stimuli to allow for female oviposition and be a suitable rearing medium for parasitoid embryonic and larval development. Diets containing insect-derived components were good elicitors for most Trichogramma species reared on artificial diets, with a few exceptions depending on the host species used or the parasitoid tested (Cônsoli 1997, Cônsoli and Parra 2000.…”
Section: Ovipositional Stimulantsmentioning
confidence: 99%